Engineering in plain sight : an illustrated field guide to the constructed environment - Hillhouse, Grady (San Francisco : No Starch Press, 2023)
"This illustrated book extends the field guide genre from natural phenomena to human-made structures, making their design and construction approachable and understandable to non-engineers. Readers will learn to identify characteristics of the electrical grid, roadways, railways, bridges, tunnels, waterways, and more"--
Electrical grid -- Communications -- Roadways -- Bridges and tunnels -- Railways -- Dams, levees, and coastal structures -- Municipal water and wastewater -- Construction.
Includes index.
Keywords: Civil engineering -- Popular works; Infrastructure (Economics) -- Popular works